Anambra State Vigilante Services and Crime Reduction in Anambra State Nigeria (2014-2022) - Gideon Chinedu Okafor; Nonso Sunday Okoye; Fidelia Nzekwe-Chinwuko; Uchenna Emmanuel Umeagugesi (Journal Majelis Paspama, 2025)
Crime remains a significant challenge to human security and development in Nigeria, including Anambra State. To address this issue, the Anambra State government established the Anambra State Vigilante Services (AVS) to complement the efforts of the Nigeria Police Force and other security agencies. This study examined the Anambra State Vigilante Services and crime reduction in Anambra State, for the period, 2014 - 2022. Specifically, the study sought to analyze the effect of collaboration between Anambra State Vigilante Services and other security agencies has reduced armed robbery and kidnapping in Anambra State. In line with the objectives of the study, one research question and hypothesis were formulated. The work is anchored on Broken Windom Theory by James Wilson and George Kelling (1982). The study adopted descriptive research design for the study. A sample of 340 drawn from a population of 340 because the population is small and manageable. Judgmental sampling techniques was used for the study. A structured Likert-type questionnaire was developed for data collection, and found reliable at Cronbach alpha coefficient of 0.80. A structured Likert-type questionnaire was developed for data collection. The econometric technique including Descriptive statistics, Pearson Product – Moment Correlation analysis was used to test the hypotheses. The findings confirms that the collaboration between Anambra State Vigilante Service and security agencies has significant effect on reduction of the rate of armed robbery and kidnapping in Anambra State, which is a crucial factor in reducing armed robbery and kidnapping in Anambra State. Based on the findings, the study concludes that Anambra State vigilante services have played a significant role in reducing crime in Anambra State. Through their community-based approach, intelligence gathering and collaboration with other security agencies. Amongst the recommendations is that Anambra State Government and security agencies should further strengthen and sustain the collaboration with Vigilante Services to leverage their community-based intelligence and enhance crime reduction efforts.